Potentially modifiable predictors of adverse neonatal and maternal outcomes in pregnancies with gestational diabetes mellitus: can they help for future risk stratification and risk-adapted patient care? - Maria-Christina Antoniou; Leah Gilbert; Justine Gross; Jean-Benoît Rossel; Céline J. Fischer Fumeaux; Yvan Vial; Jardena J. Puder (BMC, 2019)
Abstract Background Gestational diabetes mellitus (GDM) exposes mothers and their offspring to short and long-term complications. The objective of this study was to identify the importance of potentially modifiable predictors of adverse outcomes in pregnancies with GDM. We also aimed to assess the relationship between maternal predictors and pregnancy outcomes depending on HbA1c values and to provide a risk stratification for adverse pregnancy outcomes according to the prepregnancy BMI (Body mass index) and HbA1c at the 1st booking. Methods This prospective study included 576 patients with GDM. Predictors were prepregnancy BMI, gestational weight gain (GWG), excessive weight gain, fasting, 1 and 2-h glucose values after the 75 g oral glucose challenge test (oGTT), HbA1c at the 1st GDM booking and at the end of pregnancy and maternal treatment requirement. Maternal and neonatal outcomes such as cesarean section, macrosomia, large and small for gestational age (LGA, SGA), neonatal hypoglycemia, prematurity, hospitalization in the neonatal unit and Apgar score at 5 min < 7 were evaluated. Univariate and multivariate regression analyses and probability analyses were performed. Results One-hour glucose after oGTT and prepregnancy BMI were correlated with cesarean section. GWG and HbA1c at the end pregnancy were associated with macrosomia and LGA, while prepregnancy BMI was inversely associated with SGA. The requirement for maternal treatment was correlated with neonatal hypoglycemia, and HbA1c at the end of pregnancy with prematurity (all p < 0.05). The correlations between predictors and pregnancy complications were exclusively observed when HbA1c was ≥5.5% (37 mmol/mol). In women with prepregnancy BMI ≥ 25 kg/m2 and HbA1c ≥ 5.5% (37 mmol/mol) at the 1st booking, the risk for cesarean section and LGA was nearly doubled compared to women with BMI with < 25 kg/m2 and HbA1c <  5.5% (37 mmol/mol). Conclusions Prepregnancy BMI, GWG, maternal treatment requirement and HbA1c at the end of pregnancy can predict adverse pregnancy outcomes in women with GDM, particularly when HbA1c is ≥5.5% (37 mmol/mol). Stratification based on prepregnancy BMI and HbA1c at the 1st booking may allow for future risk-adapted care in these patients.